Reduced Luteinizing Hormone Induction Following Estrogen and Progesterone Priming in Female-to-Male Transsexuals - Funabashi, Toshiya; Sakakibara, Hideya; Hirahara, Fumiki; Kimura, Fukuko (Frontiers in Endocrinology, 2018)
Anatomical studies have suggested that one of the brain structures involved in gender identity is the bed nucleus of the stria terminalis, though this brain structure is probably not the only one to control gender identity. We hypothesized that, if this brain area also affected gonadotropin secretion in humans, transsexual individuals might produce different gonadotropin levels in response to exogenous stimulation. In the present study, we examined whether estrogen combined with progesterone might lead to a change in luteinizing hormone (LH) secretion in female-to-male (FTM) transsexual individuals. We studied female control subjects (n = 9), FTM transsexual subjects (n = 12), and male-to-female (MTF) transsexual subjects (n = 8). Ethinyl estradiol (50 μg/tablet) was administered orally, twice a day, for five consecutive days. After the first blood sampling, progesterone (12.5 mg) was injected intramuscularly. Plasma LH was measured with an immunoradiometric assay. The combination of estrogen and progesterone resulted in increased LH secretion in female control subjects and in MTF subjects, but this increase appeared to be attenuated in FTM transsexual subjects. In fact, the %LH response was significantly reduced in FTM subjects (P < 0.05), but not in MTF subjects (P > 0.5), compared to female control subjects. In addition, the peak time after progesterone injection was significantly delayed in FTM subjects (P < 0.05), but not in MTF subjects (P > 0.5), compared to female control subjects. We then compared subjects according to whether the combination of estrogen and progesterone had a positive (more than 200% increase) or negative (less than 200% increase) effect on LH secretion. A χ2 analysis revealed significantly different (P < 0.05) effects on LH secretion between female controls (positive n = 7, negative n = 2) and FTM transsexual subjects (positive n = 4, negative n = 8), but not between female controls and MTF transsexual subjects (positive n = 7, negative n = 1). Thus, LH secretion in response to estrogen- and progesterone priming was attenuated in FTM subjects, but not in MTF subjects, compared to control females. This finding suggested that the brain area related to gender identity in morphological studies might also be involved in the LH secretory response in humans. Thus, altered brain morphology might be correlated to altered function in FTM transsexuals.